Urban Modernization and Social Exclusion in Cartagena de Indias, a View from the Local News - Valdelamar Villegas, Fabricio Fabián (Universidad del Rosario, 2017)
Alpha. The Pearson plan of 1 914 and the Master Plan of 1 948 constituted the horizons of the urban plan of the city of Cartagena de Indias during the first half of the 20th Century. The purposeof both plans, despite their particular dispositions, was oriented to the modernization of the urban environment. A venture that, in the idea of the local and national elites, was guaranteed since both city plans accommodated to the Eurocentric urban models and prioritized the morphologic component. The axes of this pretended restoration were the sanitization, the public service implementation and the urban equipment. The adaptation of the urban superstructure and the infrastructure would be the foundation for the economic lift off that for decades eluded the city. However, the authorities’ idea —formulated in the Pearson plan and in the Master plan— would contrast with the critical view of the local news, which in many moments, served as political opposition, and in other cases portrayed, through its writing, the verisimilitudes of a city where the exclusion was the outstanding trait of its social life.